HUBUNGAN TINGKAT PENGETAHUAN PERAWAT DENGAN PENATALAKSANAAN HENTI JANTUNG (CARDIAC ARREST) DI RS CIBITUNG MEDIKA 2023 - priyanto, wandi (Jurnal Ayurveda Medistra, 2024)
Background : Indonesia currently still ranks first in the group of deaths due to non-communicable diseases, according to information provided by the results (Ministry of Health of the Republic of Indonesia, 2018). In the assessment of the fatality rate from the causes of death (Case Fatality Rate), one of the number one causes of death in non-communicable diseases is cardiovascular disease. The prevalence (cardiac arrest) in Indonesia ranges from 10 out of 10,000 normal people under 35 years of age and each year can reach 300,000-350,000 incidents (PERKI, 2017). (Nugroho & Muhammad, 2022). Research Objective: To determine the relationship between the level of knowledge of nurses and the management of cardiac arrest at Cibitung Medika Hospital in 2023. Research Method : This research uses a correlational analytical design with a cross-sectional approach, namely a type of research that emphasizes measuring/observing independent and dependent variable data only once at a time (Nursalam, 2020). Research Results : The results of the research carried out obtained the results of the Chi Square statistical test, namely the Asymp Significance value (0.000) < α value (0.05), this shows that H0 was rejected and the output results of the Chi Square statistical test obtained the calculated x2 value ( 143.391a) > x2 table (94.99), this shows that H0 is rejected. Thus, it can be concluded that there is a relationship between the level of knowledge and the management of cardiac arrest at Cibitung Medika Hospital 2023. Conclusion : There is a relationship between the level of knowledge of nurses and the management of cardiac arrest at Cibitung Medika Hospital 2023. Keywords: Knowledge, Cardiac arrest.